Anthracoidea caricis-reznicekii (Anthracoideaceae), a new species on Carex reznicekii, and A. eburneae, a new record for the USA - Denchev, Teodor T.; Denchev, Cvetomir M. (Phytotaxa, 2016)
A new ovariicolous smut fungus, Anthracoidea caricis-reznicekii on Carex reznicekii (C. sect. Acrocystis), is described and illustrated from the USA. The new species is compared with the known Anthracoidea species on sedges in Carex sect. Acrocystis and other closely related sections. Anthracoidea caricis-reznicekii is characterized by a complex of characters: medium-sized spores (15–24.5 μm long), thick spore wall (up to 6.0 μm thick), with conspicuous, often numerous (up to 8) protuberances, and warts 0.2–0.5 μm high. A key to the four known Anthracoidea species on sedges in section Acrocystis is provided. Anthracoidea eburneae, previously known only from Canada, is reported for the first time from the USA, on Carex eburnea.